Genotypic diversity and phenotypic traits of Streptococcus mutans isolates and their relation to severity of early childhood caries - Valdez, Remberto Marcelo Argandoña [UNESP]; Duque, Cristiane [UNESP]; Caiaffa, Karina Sampaio [UNESP]; dos Santos, Vanessa Rodrigues [UNESP]; de Aguiar Loesch, Maria Luiza [UNESP]; Colombo, Natalia Helena [UNESP]; Arthur, Rodrigo Alex; Negrini, Thais de Cássia; Boriollo, Marcelo Fabiano Gomes; Delbem, Alberto Carlos Botazzo [UNESP] (Springer Nature, 2017)
Background: Early childhood caries (ECC) is an aggressive condition that can affect teeth of young children. This study aimed to evaluate genotypic diversity and phenotypic traits of S. mutans isolated from dental biofilms of children with different caries status in comparison with caries free (CF) children. Methods: Streptococcus mutans strains were isolated from supragingival biofilm samples of CF, ECC and severe-ECC (S-ECC) children and genotyped by arbitrary-primer polymerase chain reaction - AP-PCR. S. mutans genotypes were tested for their ability to reduce the suspension pH through glycolysis, to tolerate extreme acid challenge and by their ability to form biofilm. Response variables were analyzed by ANOVA/Tukey or Kruskal-Wallis/Mann-Whitney tests at a 5% of significance. Results: There was an increase in the prevalence of Streptococcus mutans in biofilms with the severity of dental caries. No differences in genotypic diversity and in acidogenicity of genotypes were found among CF, ECC and S-ECC children. S mutans strains with genotypes more characteristic for ECC and S-ECC children formed more biofilms than those identified in CF children. The strains isolated from S-ECC children were highly acid tolerant. Conclusion: Although S. mutans genotypic diversity was similar among the groups of children, phenotypic traits of S. mutans, especially the acid tolerance response, could explain the severity of early childhood caries.
Keywords: Acidogenicity; Aciduricity; Dental biofilm; Early childhood caries; Genotypic diversity; Streptococcus mutans